2007
DOI: 10.1074/jbc.m700656200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Selectivity of Nucleoside Triphosphate Incorporation Opposite O6-Benzylguanine by Sulfolobus solfataricus DNA Polymerase Dpo4

Abstract: Previous work has shown thatAlkyl and aryl modifications are some of the most extensively studied forms of DNA damage (1), with O 6 -alkylation providing one of the more mutagenic examples of this type of lesion (2, 3). Alkylating agents have been used in warfare (i.e. mustard gas), and they also continue to be used in chemotherapeutic regimes (4 -6). Endogenous sources of DNA alkylation can arise through nonenzymatic methylation by S-adenosylmethionine, although O 6 -alkylation is presumed to occur to only tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
92
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(111 citation statements)
references
References 36 publications
19
92
0
Order By: Relevance
“…Similarly in the case of S. solfataricus Dpo4, hydrogen bonding is more important than base pair geometry for nucleotide selectivity opposite O 6 -methylG. The crystal structures of Dpo4 with O 6 -methylG and O 6 -benzylG have shown that a wobble base pair forms when dCTP pairs opposite the lesion (13,16). However, unlike pol , Dpo4 utilizes wobble base pairing to preferentially incorporate dCTP opposite O 6 -methylG, thus maintaining high fidelity during lesion bypass (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in the case of S. solfataricus Dpo4, hydrogen bonding is more important than base pair geometry for nucleotide selectivity opposite O 6 -methylG. The crystal structures of Dpo4 with O 6 -methylG and O 6 -benzylG have shown that a wobble base pair forms when dCTP pairs opposite the lesion (13,16). However, unlike pol , Dpo4 utilizes wobble base pairing to preferentially incorporate dCTP opposite O 6 -methylG, thus maintaining high fidelity during lesion bypass (13).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of the Y-family DNA polymerase Sulfolobus solfataricus Dpo4 revealed wobble base pairing of cytosine opposite O 6 -methylG (13). The NMR results and crystal structures demonstrate that the O 6 -methylG:T base pair forms a pseudo Watson-Crick pair, with a single hydrogen bond formed between the O2 atom of T and the N2 atom of O 6 -methylG (11,13,14,16). The shape of the Watson-Crick-like O 6 -methylG:T base pair fits in the active site of the DNA polymerase without distorting the DNA, thereby contributing to the incorporation of dTTP opposite the lesion (17).…”
mentioning
confidence: 97%
“…Dpo4 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)). In fact, the asymmetric loss of efficiency observed with Klenow fragment (large for d(DFT)TP:A and small for dATP:DFT) could be due to different influences of hydrogen bonds from polymerase residues to template and dNTP bases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, once the template 8-oxoG:A base pair is incorporated into DNA and is at the template-primer terminus during DNA synthesis, it is well-extended by DNA polymerases facilitating G to T mutagenesis. The structural basis for DNA polymerase preferences in mutagenic bypass of the 8-oxoG lesion is emerging across the DNA polymerase families (8)(9)(10)(11)(12) and is the subject of the present report.…”
mentioning
confidence: 99%